Handling Cases of Sexual Violence against Children in North Aceh Regency (Overview: Law Number 23 Year 2002 and Aceh Qanun Number 11 Year 2008 Concerning Children Protection) - Abdullah Abdullah (Budapest International Research and Critics University, 2020)
The impact of sexual violence in northern Aceh has destroyed the rule of law, individual rights and social order, through writing it will describe and analyze efforts to handle cases of sexual violence against children in the northern Aceh district. This type of research includes normative juridical research in which qualitative information and research data are mostly in the form of texts and a number of case studies. The results showed that: sexual violence against children in the district of North Aceh, namely rape, sexual harassment, sodomy, incest, escaping underage girls, molestation and intimidation. Adult actors sometimes have blood relations, kinship, educational relationships and have intimate relationships. Forms of handling cases by social services under the control of P2TP2A service units in collaboration or in partnership with various parties / institutions starting with assistance in the community, psychological recovery of victims, bringing victims to the doctor for vise and then proceed to the police station, continued to assist until the legal process in court there is legal certainty then the next handling will be handled by the government through the North Aceh district social service by maintaining security, fulfillment of restitution rights for victims, but this hope has not been realized maximally because the North Aceh district government has not made a comprehensive program for rehabilitation of victims, generally victims handed over to the family and facilitated to be entrusted in the salafi boarding school (traditional).